The Effect of Brand Image, Brand Personality and Brand Awareness on Purchase Intention of Local Fashion Brand â€œThis Is Aprilâ€ - Tsabitah, Naurah; Anggraeni, Rila (KINERJA, 2021)
The fashion industry is one of the sectors in the creative economy. In 2019, the Indonesian Ministry of Industry revealed that the clothing industry recorded the largest export value. Therefore, business activists are competing to create local fashion brands and take steps to create purchase intention. This study aims to determine the impact of brand image, brand personality, and brand awareness on purchase intention Local Fashion Brand â€œThis Is Aprilâ€ in Malang City. This is explanatory research type with a quantitative approach. The samples are 160 respondents. The sampling method is non-probability sampling with purposive sampling technique. The data collection method is questionnaire distributed online. This study used multiple linear regression analysis methods using IBM SPSS software. This study findings show that brand personality and brand awareness have a significant effect on purchase intention. Meanwhile, brand image has no effect on purchase intention. This study suggested that the company should maintain and increasing brand personality and brand awareness by, among others, following the fashion trends, project endorsement and collaboration with influencers to creat purchase intention.Â Keywords: Brand Image, Brand Persoanlity, Brand Awareness, Purchase Intention